Seroprotection against serogroup C meningococcal disease in adolescents in the United Kingdom: observational study. Issue 7659 (5th June 2008) - Snape, M D; Kelly, D F; Lewis, S; Banner, C; Kibwana, L; Moore, C E; Diggle, L; John, T; Yu, L M; Borrow, R; Borkowski, A; Nau, C; et al.
Abstract : Objective To determine the persistence of bactericidal antibody titres following immunisation with serogroup C meningococcal glycoconjugate vaccine at age 6-15 years in order to examine changes in persistence of antibodies with age. Design Observational study. Setting Secondary and tertiary educational institutions in the United Kingdom. Participants Healthy adolescents aged 11-20 years previously immunised between 6 and 15 years of age with one of the three serogroup C meningococcal vaccines. Intervention Serum obtained by venepuncture. Main outcome measures Percentage of participants with (rabbit complement) serum bactericidal antibody titres of at least 1:8; geometric mean titres of serogroup C meningococcal serum bactericidal antibody. Results Five years after immunisation, 84.1% (95% confidence interval 81.6% to 86.3%) of 987 participants had a bactericidal antibody titre of at least 1:8. Geometric mean titres of bactericidal antibody were significantly lower in 11-13 year olds (147, 95% confidence interval 115 to 188) than in 14-16 year olds (300, 237 to 380) and 17-20 year olds (360, 252 to 515) (P<0.0001 for both comparisons). Within these age bands, no significant difference in geometric mean titres of bactericidal antibody between recipients of the different serogroup C meningococcal vaccines was seen. More than 70% of participants had received a vaccine from one manufacturer; in this cohort, geometric mean titres were higher in those immunised at aged 10 years or above than in those immunised before the age of 10. Conclusions Higher concentrations of bactericidal antibody are seen five years after immunisation with serogroup C meningococcal vaccine at age 10 years or above than in younger age groups, possibly owing to immunological maturation. This provides support for adolescent immunisation programmes to generate sustained protection against serogroup C meningococcal disease not only for the vaccine recipients but also, through the maintenance of herd immunity, for younger children.